Characteristics of Project Organisations of the Japanese Construction Industry Focusing on the Modularity of Components - Yoshida, Satoshi (Frontiers in Built Environment, 2022)
Currently, technologies related to the construction industry have increased in their complexities and garnered important advancements. However, the pandemic upset the entire structure of industries, including the construction industry. Hence, a precise prescription is required for a right future direction of the construction industry. This study aims to provide a method for understanding the fundamental characteristics of the building industry via industrial analysis. In this article, the ‘Architecture concept’ is adopted as an academic tool of consideration and is carried out a practical analysis on the building industry to provide a novel perspective. Previous studies analyzed several industries in this ‘architectural concept.’ However, the analysis based on this concept has not progressed significantly for the building industry. Because this concept was created focusing on architecture, it has a high affinity with the building industry. Therefore, with the cooperation of multiple experts, we categorized the building components and modularization of the production process according to the selected indicators; then, we investigated the trends of the entire Japanese building industry. By analyzing the results of this survey, one can understand the basic correlation between the physical modularity of components and the independence of the design information creation process. This study contributes to providing the method to understanding the fundamental characteristics of the building industry and provides to presents the possibility of inter-industry and inter-regional comparisons from this perspective.